2008
DOI: 10.1063/1.2838180
|View full text |Cite
|
Sign up to set email alerts
|

Etching characteristics of LiNbO3 in reactive ion etching and inductively coupled plasma

Abstract: The etching characteristics of congruent LiNbO3 single crystals including doped LiNbO3 and proton-changed LiNbO3 have been studied in reactive ion etching (RIE) and inductively coupled plasma (ICP) etching tools, using different recipes of gas mixtures. The effects of parameters including working pressure, RIE power, and ICP power are investigated and analyzed by measurement of etching depth, selectivity, uniformity, etched surface state, and sidewall profile by means of focused ion beam etching, energy-disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…The substrate was selectively removed using reactive ion etching (RIE) and inductive coupled plasma (ICP) etching tools with a hybrid of SF 6 /Ar gases. ICP etching of the LiNbO 3 has reached ∼200 nm/min at 1000 W ICP with selectivity to Ni being ∼10 [11]. The final nano-pillars of LiNbO 3 achieved by this NIL approach can be seen in Fig 1. Typical nano-pillar heights achieved were 500 nm to 1 µm with a pitch equivalent to the imprint master (600 nm).…”
Section: Nanoimprinting Ferroelectricsmentioning
confidence: 95%
“…The substrate was selectively removed using reactive ion etching (RIE) and inductive coupled plasma (ICP) etching tools with a hybrid of SF 6 /Ar gases. ICP etching of the LiNbO 3 has reached ∼200 nm/min at 1000 W ICP with selectivity to Ni being ∼10 [11]. The final nano-pillars of LiNbO 3 achieved by this NIL approach can be seen in Fig 1. Typical nano-pillar heights achieved were 500 nm to 1 µm with a pitch equivalent to the imprint master (600 nm).…”
Section: Nanoimprinting Ferroelectricsmentioning
confidence: 95%
“…It is far less developed for piezoelectric materials and typically based on reactive ion etching (RIE) [e.g. [6][7][8][9]. LiNbO 3 is the more appropriate material from the electroacoustic point of view; however, it is more challenging than quartz.…”
Section: Technology Developmentmentioning
confidence: 99%
“…RIE is in itself a highly controllable and versatile dry process involving both physical and chemical effects to achieve directive and anisotropic material removal. It has already been demonstrated that lithium niobate can be dry etched using fluorine-based chemistries, [14][15][16][17] and ICP-RIE has previously been used on X-or Z-axis crystallographic orientations of lithium niobate to successfully fabricate ridge waveguides or photonic crystals, usually after proton exchange [18][19][20] but there is no report of any specific process allowing to dry etch structures that are several microns in depth in lithium niobate. The fabrication of very deep or very high aspect ratio structures is actually seriously impaired by the formation of lithium fluoride ͑LiF͒ compounds during the etching process that are relatively nonvolatile, leading to redeposition phenomena impeding the material removal.…”
Section: Introductionmentioning
confidence: 98%